2010
DOI: 10.1093/jac/dkq009
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus with reduced glycopeptide susceptibility in Liverpool, UK

Abstract: Laboratory strategies to reduce morbidity associated with hGISA should focus on testing for hGISA in bacteraemic (rather than colonizing) MRSA isolates in patients with recurrent S. aureus bacteraemia following glycopeptide exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Most previous studies have focused on hVISA and VISA strains isolated from blood [24,25]. Recently, Hu and colleagues found that hVISA and VISA strains were identified from diverse infection sites, predominantly from sputum (56.3%), followed by pus (18.8%), blood (8.8%), secretions (6.3%), drainage (3.8%), and other (6.3%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have focused on hVISA and VISA strains isolated from blood [24,25]. Recently, Hu and colleagues found that hVISA and VISA strains were identified from diverse infection sites, predominantly from sputum (56.3%), followed by pus (18.8%), blood (8.8%), secretions (6.3%), drainage (3.8%), and other (6.3%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, clinical isolates of S. aureus with decreased susceptibility to vancomycin have been reported in many countries, including the United Satates [3,4], Canada [5], China [6], South Korea [6], United Kingdom [7,8], Italy [9], and France [10], and their occurrence has become a major concern throughout the world. Additionally, in 2002, the first vancomycin-resistant S. aureus (VRSA) strain was reported in the Jung Wook Kim, et al : Molecular Characteristics and Resistance Profiles of VISA 89…”
Section: Introductionmentioning
confidence: 99%
“…The strains positive with agar screening method were subjected to macro Etest and subpopulation analysis. These methods are reliable and sensitive to detect hGISA (Kirby et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, GRSA, GISA and hGISA have increasingly been reported (Kirby et al, 2010). hGISA strains are defined as for which vancomycin MICs are 1 to 4 µg mL −1 but which contain subpopulations that can grow on agar plates supplemented with 4 mg of vancomycin per liter (Satola et al, 2011).…”
Section: Introductionmentioning
confidence: 99%